2021
DOI: 10.1038/s41467-021-26294-9
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization between peripheral circadian clock and feeding-fasting cycles in microfluidic device sustains oscillatory pattern of transcriptome

Abstract: The circadian system cyclically regulates many physiological and behavioral processes within the day. Desynchronization between physiological and behavioral rhythms increases the risk of developing some, including metabolic, disorders. Here we investigate how the oscillatory nature of metabolic signals, resembling feeding-fasting cycles, sustains the cell-autonomous clock in peripheral tissues. By controlling the timing, period and frequency of glucose and insulin signals via microfluidics, we find a strong ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 73 publications
4
13
0
Order By: Relevance
“…We used a U2OS Bmal1 - dLuc reporter cell line to compare rhythms in high versus low glucose medium and found a slight under-compensation phenotype (Supplementary Figure 6), similar to the single-cell rhythms report (Gagliano et al, 2021). Period length was 0.5 hours shorter in 25 mM (high) glucose compared to 5.56 mM (low) glucose, trending in the same direction as the ∼1.5-hour period shortening seen for the wild-type Neurospora clock across glucose concentrations (Figures 1 – 3).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…We used a U2OS Bmal1 - dLuc reporter cell line to compare rhythms in high versus low glucose medium and found a slight under-compensation phenotype (Supplementary Figure 6), similar to the single-cell rhythms report (Gagliano et al, 2021). Period length was 0.5 hours shorter in 25 mM (high) glucose compared to 5.56 mM (low) glucose, trending in the same direction as the ∼1.5-hour period shortening seen for the wild-type Neurospora clock across glucose concentrations (Figures 1 – 3).…”
Section: Resultssupporting
confidence: 77%
“…We used a U2OS Bmal1-dLuc reporter cell line to compare rhythms in high versus low glucose medium and found a slight under-compensation phenotype (Supplementary Figure 6), similar to the single-cell rhythms report (Gagliano et al, 2021). Period length was 0. among the hits from a genome-wide screen for period length defects using U2OS cells (Zhang et al, 2009) or tested in a kinase/phosphatase siRNA screen (Maier et al, 2009); however, visual inspection of the genome-wide screen data confirmed that a subset of the pooled siRNAs did show period effects after CPSF6 or SETD2 knockdown (source: BioGPS database, "Circadian Genomics Screen" plugin).…”
Section: Mutantssupporting
confidence: 66%
“…To reach this aim we take advantage of microfluidics technology applied in circadian studies as we recently reported. Microfluidic technology enables timely hepatic differentiation [21] combined with tight temporal control of the microenvironment [6]. This is an essential prerequisite for the synchronization of the cellautonomous circadian clock of differentiating cells.…”
Section: Discussionmentioning
confidence: 99%
“…Microfluidic devices were fabricated by standard softlithographic techniques as previously described [6]. The master mold was photo-lithographically patterned using a SU8-2100 (Microchem) negative photoresist to obtain a final thickness of 200 mm.…”
Section: Microfluidic Device Fabricationmentioning
confidence: 99%
See 1 more Smart Citation